Untitled - Eisvran, Jayseellan (2016)
UNTITLED is an interactive installation that visualizes communications that happens in an organization. The visualization is realized through the coloured paths created between mirrors and the different coloured lasers. The installation is intended as a form of reflection on society and the communications that occur within organizations.